Analisis Faktor-Faktor Yang Mempengaruhi Produk Domestik Regional Bruto (Pdrb) Di Kawasan Subosukowonosraten Surakarta, Boyolali, Sukoharjo,Karanganyar, Wonogiri, Sragen, Klaten) Provinsi Jawa Tengah - , Untari, Dr. Daryono Soebagyo, M.Ec (2017)
Local economic development in the era of regional autonomy facing both internal and external challenges such as climate inequalities and globalization. Gaps and globalization has implications for the region to implement the acceleration of regional economic development is focused through the region and its flagship product. Subosukowonosraten in Central Java region is an area that has a Gross Domestic Income which is always a good relative naik.Kerjasama between regions alone is expected to create equitable growth so that the regional economic growth in the region could be more advanced Subosukowonosraten and evenly. This study aimed to determine the effect of regional revenue to GDP in Region Subosukowonosraten, determine the effect of local expenditure to GDP in Subosukowonosraten Region, and determine the effect of Labor to GDP in Subosukowonosraten Region. The method in this research using panel data regression analysis using a model of REM (Random Effect Method). From the results of the study showed that the variable PAD positive and significant impact to the GDP Regency / City in Region Subosukowonosraten, variable local expenditure has positive effect but not significantly to the GDP in Region Subosukowonosraten, while the variable Labor positive effect but not significantly to the GDP Regency / City in Region Subosukowonosraten.